2010
DOI: 10.3390/ph3051530
|View full text |Cite
|
Sign up to set email alerts
|

Nonsteroidal Anti-Inflammatory Drugs (NSAIDs): Progress in Small Molecule Drug Development

Abstract: Ever since the discovery of aspirin, small molecule therapeutics have been widely prescribed to treat inflammation and pain. Aspirin and several small molecule NSAIDs are known to inhibit the enzymes cyclooxygenase-1 (COX-1) and -2 (COX-2). Despite the success of NSAIDs to treat inflammatory disorders, the development of a clinically useful small molecule NSAIDs with decreased side effect profiles is an ongoing effort. The recent discovery and development of selective COX-2 inhibitors was a step toward this di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 91 publications
(111 reference statements)
4
62
0
5
Order By: Relevance
“…As visible, with exception of 8, all phenolics identified in Scorzonera aerial part extracts are glycosides, in majority flavonoids. The presence of all these compounds (1)(2)(3)(4)(5)(6)(7)(8) in the most active extracts (Ex. 1 and Ex.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As visible, with exception of 8, all phenolics identified in Scorzonera aerial part extracts are glycosides, in majority flavonoids. The presence of all these compounds (1)(2)(3)(4)(5)(6)(7)(8) in the most active extracts (Ex. 1 and Ex.…”
Section: Resultsmentioning
confidence: 99%
“…From the above mentioned, we suggested that chlorogenic acid (8), derivatives of dicaffeoyl-quinic acid (6 and 7), and flavonoids, especially quercetin-3-O-β-D-glucoside (1) and hyperoside (2) could be responsible for the anti-inflammatory activity of tested extracts. Therefore, further experiments were carried out with phenolic compounds previously obtained from Scorzonera species (1)(2)(3)(4)(5)(6)(7)(8), to assay the inhibition of TNF-α and IL-1β production in THP-1 cells, and later also with triterpenes 9-16, because taraxasterol acetate (9) isolated from S. latifolia showed previously analgesic activity in vivo in writhing and tail-flick tests [21] and also other triterpenoid substances like lupeol derivatives (10 and 11), β-sitosterol (12) and other triterpenes (13)(14)(15)(16) could potentially demonstrate anti-phlogistic effect [38,39]. Unfortunately, only weak activity of compounds tested was observed, and no statistically significant activity has been observed in comparison with standard used (prednisone, Supplementary Materials, Figure S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…NSAIDs are characterized in two distinct classes according to their ability to selectively block COX-2 and this is given by the ratio of the IC50 for COX-1 and COX-2 with in vitro studies [22][23][24]: a) Non-selective COX inhibitors: block both COX-1 and COX-2 in a non-selective manner. They traditionally possess a carboxylic acid (-COOH) as a functional group and represent the most prescribed NSAIDs for fever, pain and inflammation treatment; b) Cox-2 selective inhibitors: selectively block COX-2.…”
Section: Interplay Between Mechanism Of Action and Therapeutic Effectsmentioning
confidence: 99%
“…[76][77][78] it has a very short half-live in blood, its oxidization to 15-ketoprostaglandins is catalyzed by 15-hydroxyprostaglandin dehydrogenase In order to design any structure with pyrrole moiety or its fused form indole, vital considerations must be taken to ensure its anti-inflammatory activity. 32,74,79,80 First, the structure should consist of an acidic moiety (carboxylic acid, enols, ester etc.) attached to a planar, aromatic functional group (appears to correlate with the double bond of AA), 31 4-benzodioxine or pyrrole nucleus are described.…”
Section: Structure-activity Relationships (Sar)mentioning
confidence: 99%